Long-term monitoring of landfast sea ice extent and thickness in Kongsfjorden, and related applications - Gerland, Sebastian; Pavlova, Olga; Divine, Dimitry; Negrel, Jean; Dahlke, Sandro; Johansson, A Malin; Maturilli, Marion; Semmling, Maximilian (Zenodo, 2020)
This is chapter 6 of the State of Environmental Science in Svalbard (SESS) report 2019 (https://sios-svalbard.org/SESS_Issue2). Landfast sea ice (ice anchored to the shore) covers the inner parts of Kongsfjorden, Svalbard, in winter and spring, and is an important feature for the physical and biological fjord systems. Systematic fast-ice monitoring for Kongsfjorden, as a part of a long-term project at the Norwegian Polar Institute (NPI), started in 2003. It includes ice extent mapping and in situ measurements of ice and snow thickness. The permanent presence of NPI staff at Ny-Ålesund Research Station enables regular in situ fast-ice thickness measurements as long as the fast ice is accessible. In addition, daily visits to the observatory on the mountain Zeppelinfjellet close to Ny-Ålesund allow regular ice observations (weather, visibility, and daylight permitting). Monitoring of the sea ice conditions in Kongsfjorden can be used to demonstrate and investigate phenomena related to climate change in the Arctic. Fjord ice begins to form in the inner part of Kongsfjorden between December and March. After that the ice grows in thickness and extent, and then decreases until it melts or breaks off and drifts out of the fjord between April and June. Before 2006, ice often stretched from the interior to the central fjord parts, but in later years the ice has mainly been restricted to the inner fjord. Moreover, the ice was usually at least 0.6 m thick, in contrast to recent years with thickness often only about 0.2 m. The snow cover thickness on the ice in spring has also decreased, which can be partly explained by shorter fast ice seasons. The reason for less ice in Kongsfjorden after 2006 is considered to be a combination of the influence of warmer water and higher air temperatures in winter. This monitoring has contributed to a number of process and validation studies, for example to improve satellite remote sensing techniques and the understanding of atmosphere–ice–ocean interaction.